CMV drives the expansion of highly functional memory T cells expressing NK-cell receptors in renal transplant recipients - Makwana, N.; Foley, B.; Fernandez, S.; Lee, S.; Irish, A.; Pircher, H.; Price, Patricia (Wiley-VCH Verlag GmbH & Co. KGaA, 2017)
Cytomegalovirus (CMV) is a common opportunistic infection encountered in renal transplant recipients (RTRs) and may be reactivated without symptoms at any time post-transplant. We describe how active and latent CMV affect T-cell subsets in RTRs who are stable on maintenance therapy. T-cell responses to CMV were assessed in RTRs (n = 54) > 2 years post-transplant, and healthy controls (n = 38). Seven RTRs had CMV DNA detectable in plasma. CMV antibody and DNA aligned with increased proportions of CD8 + T cells and reduced CD4/CD8 ratios. This paralleled an expansion of effector memory T-cell (T EM ), terminally differentiated T-cell (T EMRA ) and CD57 + T EMRA cell populations. Expression of NK-cell receptors, LIR-1 and KLRG1 on CD4 + and CD8 + CD57 + T EM and T EMRA cells correlated with elevated interferon-? and cytotoxic responses to anti-CD3 and increased cytotoxic responses to CMV phosphoprotein (pp) 65 in RTRs who carried CMV DNA. CD8 + T cells from all CMV seropositive RTRs responded efficiently to CMV immediate early (IE) -1 peptides. The data show that latent and active CMV infection can alter T-cell subsets in RTRs many years after transplantation, and up-regulate T-cell expression of NK-cell receptors. This may enhance effector responses of CD4 + and CD8 + T cells against CMV.